Стан ниркової функції у чоловіків із гіпертонічною хворобою в умовах порушень пуринового та вуглеводного обміну - Колесник, Михайло Юрійович; Дудко, О. В.; Kolesnyk, M. Yu.; Dudko, O. V. (Запорізький державний медичний університет, 2022)
Мета роботи – оцінити стан ниркової функції в чоловіків із гіпертонічною хворобою в умовах порушення пуринового та вуглеводного обміну. Матеріали і методи. У 60 пацієнтів чоловічої статі (вік – 18–65 років) із гіпертонічною хворобою І–ІІ стадій, порушеннями пуринового та вуглеводного обміну визначали рівень сечової кислоти (СК) добової сечі, фракційної екскреції СК, креатиніну добової сечі, мікроальбуміну в сечі та рівень цистатину С. Для дослідження гемодинаміки виконали добове моніторування артеріального тиску (АТ). Оцінювання показників кінетики та деформації міокарда – в режимі offline за допомогою інтегрованого до ультразвукового приладу пакету програм Xstrain (Esaote, Італія). Пацієнтів поділили на 2 клінічні групи: 1 – гіпертонічна хвороба (ГХ) із гіперурикемією; 2 – ГХ без урикемії. Статистичний аналіз результатів виконали, використавши пакет програм Statistica 13.0 (Statsoft, США). Результати. У хворих 1 групи встановили достовірно вищий рівень мікроальбуміну сечі та вірогідне зниження показника фракційної екскреції СК (р < 0,001) порівняно з пацієнтами 2 групи. Це вказує на погіршення ниркової функції в умовах гіперурикемії. Aim. To assess the condition of renal function in hypertensive men in conditions of disorders of purine and carbohydrate metabolism Material and methods. 60 male patients (aged from 18 to 65 years) with stage I–II of arterial hypertension (AH) and purine and carbohydrate metabolism disorders were examined. In these patients, the level of uric acid (UA) in daily urine, fractional excretion of UA, creatinine in daily urine, microalbumin in urine and the cystatin C level were determined. Hemodynamics was studied by daily blood pressure monitoring. Assessment of kinetics and deformation of the myocardium in offline mode using the Xstrain software package integrated into the ultrasound device (Esaote, Italy) was made. Patients were divided into 2 clinical groups – 1 group of AH with hyperuricemia, 2 – AH without uricemia. Statistical analysis of the results was performed using the Statistica 13.0 software package (Statsoft, USA). Results. Correlation analysis in group 1 showed a positive correlation of cystatin C with the average daytime systolic blood pressure (SBP) (r = 0.408) and the variability of diastolic blood pressure (DBP) at night (r = 0.405), urinary microalbumin with the average SBP at night (r = 0.390) and average pulse blood pressure (r = 0.402), LV posterior wall thickness (r = 0.438), LV myocardial mass index (r = 0.621), end-diastolic index (EDI) (r = 0.492), end-systolic index (ESI) (r = 0.426), LV anterior-posterior size (r = 0.385). A negative correlation was established between blood serum SC and ejection fraction (EF) of the LV (r = -0.410), urinary microalbumin with cardiac index (SI) (r = -0.555) and the speed of movement of the lateral (e’ lat) part of the annulus fibrosus mitral valve (r = -0.453).
The renal function in men with hypertension in conditions of purine and carbohydrate metabolism disorders
Колесник М. Ю. - ORCID ID: 0000-0001-7566-1899; Дудко О. В. - ORCID ID: 0000-0002-0367-6300.
Keywords: гіпертонічна хвороба; ниркова функція; гіперурикемія; гіперглікемія; мікроальбумінурія; arterial hypertension; kidney function; hyperuricemia; hyperglycemia; microalbuminuria